Case Usage Errors Among Foreign Students - Inamova Nargiza Odilovna (International Journal Of Literature And Languages, 2026)
The correct use of grammatical case remains one of the most challenging aspects of second language acquisition for foreign students. This study investigates common case usage errors produced by foreign learners and identifies their linguistic causes and pedagogical implications. Using an error-analysis approach, students’ written texts and spoken samples were examined to classify types of case-related errors and determine patterns influenced by first-language transfer, overgeneralization, and incomplete rule acquisition. The findings reveal that case substitution, omission, and overextension represent the most frequent error categories. The study highlights the importance of targeted corrective feedback and contrastive teaching strategies to reduce case-related errors in foreign language classrooms.